The X-linked 1.688 Satellite in Drosophila melanogaster Promotes Specific Targeting by Painting of Fourth. Issue 2 (1st February 2018) - Kim, Maria; Ekhteraei-Tousi, Samaneh; Lewerentz, Jacob; Larsson, Jan
Abstract: Repetitive DNA, represented by transposons and satellite DNA, constitutes a large portion of eukaryotic genomes, being the major component of constitutive heterochromatin. There is a growing body of evidence that it regulates several nuclear functions including chromatin state and the proper functioning of centromeres and telomeres. The 1.688 satellite is one of the most abundant repetitive sequences in Drosophila melanogaster, with the longest array being located in the pericentromeric region of the X-chromosome. Short arrays of 1.688 repeats are widespread within the euchromatic part of the X-chromosome, and these arrays were recently suggested to assist in recognition of the X-chromosome by the dosage compensation male-specific lethal complex. We discovered that a short array of 1.688 satellite repeats is essential for recruitment of the protein POF to a previously described site on the X-chromosome ( PoX2 ) and to various transgenic constructs. On an isolated target, i.e., an autosomic transgene consisting of a gene upstream of 1.688 satellite repeats, POF is recruited to the transgene in both males and females. The sequence of the satellite, as well as its length and position within the recruitment element, are the major determinants of targeting. Moreover, the 1.688 array promotes POF targeting to the roX1 -proximal PoX1 site in trans . Finally, binding of POF to the 1.688-related satellite-enriched sequences is conserved in evolution. We hypothesize that the 1.688 satellite functioned in an ancient dosage compensation system involving POF targeting to the X-chromosome.